Legal Certainty in The Implementation Of Sales Tax For E-Commerce Businesses - Tumimbang, Wilmar; Hasibuan , Fauzie Yusuf; Hansaontha , Prachya (CV. Era Digital Nusantara, 2024)
This research aims to analyse the legal certainty in the application of Value Added Tax (VAT) on e-commerce transactions in Indonesia. Using a normative juridical approach with a qualitative descriptive method, this research evaluates the implementation of applicable tax regulations, particularly the Minister of Finance Regulation Number 60/PMK.03/2022, which regulates VAT obligations for e-commerce businesses. The results show that despite clear regulations, the implementation of VAT in the e-commerce sector still faces obstacles, such as the lack of understanding of business actors, especially MSMEs, regarding their tax obligations. In addition, challenges arise from unclear rules regarding cross-border transactions as well as entrepreneurs who are not registered as Taxable Entrepreneurs (PKP). Therefore, this study recommends the need for strengthening regulations, more intensive socialisation to business actors, and increased supervision so that tax compliance can be maximised, so that the e-commerce sector can make a greater contribution to the Indonesian economy.